Fecal supernatants from dogs with idiopathic epilepsy activate enteric neurons - Elfers, Kristin; Watanangura, Antja; Hoffmann, Pascal; Suchodolski, Jan S.; Khattab, Mohammad R.; Pilla, Rachel; Meller, Sebastian; Volk, Holger A.; Mazzuoli-Weber, Gemma (Frontiers in Neuroscience, 2024)
Alterations in the composition and function of the gut microbiome have been reported in idiopathic epilepsy (IE), however, interactions of gut microbes with the enteric nervous system (ENS) in this context require further study. This pilot study examined how gastrointestinal microbiota (GIM), their metabolites, and nutrients contained in intestinal contents communicate with the ENS. Faecal supernatants (FS) from healthy dogs and dogs with IE, including drug-naïve, phenobarbital (PB) responsive, and PB non-responsive dogs, were applied to cultured myenteric neurons to test their activation using voltage-sensitive dye neuroimaging. Additionally, the concentrations of short-chain fatty acids (SCFAs) in the FS were quantified. Our findings indicate that FS from all examined groups elicited neuronal activation. Notably, FS from PB non-responsive dogs with IE induced action potential discharge in a higher proportion of enteric neurons compared to healthy controls, which exhibited the lowest burst frequency overall. Furthermore, the highest burst frequency in enteric neurons was observed upon exposure to by FS from drug-naïve dogs with IE. This frequency was significantly higher compared to that observed in PB non-responsive dogs with IE and showed a tendency to surpass that of healthy controls. Although observed disparities in SCFA concentrations across the various FS samples might be associated with the induced neuronal activity, a direct correlation remains elusive at Faecal Supernatants Activate Enteric Neurons 2 this point. The obtained results hint at an involvement of the ENS in canine IE and set the basis for future studies.